Bridging Radiology and Pathology: ATRX Loss and T2-FLAIR Mismatch as Early Diagnostic and Prognostic Markers in Diffuse Gliomas - Quratulain Tariq; Eisha Abid Ali; Rahamah Arshad; Ahmad Sohail; Irfan Yousaf; Muhammad Shahzad Shamim (Journal of the Pakistan Medical Association, 2025)
ATRX mutation and the T2-FLAIR mismatch sign haveemerged as complementary molecular and imagingmarkers in diffuse gliomas. ATRX loss defines IDH-mutantastrocytoma at the molecular level, while the mismatchsign provides a non-invasive radiological clue with highspecificity but limited sensitivity. Used together, theyimprove diagnostic precision, refine prognosticassessment, and guide individualized treatmentplanning. Keywords: ATRX mutation, T2-FLAIR mismatch sign,Astrocytoma, Oligodendroglioma